Physical fitness of individuals with intellectual disability who have Special Olympics experience - Rintala, Pauli; Asunta, Piritta; Lahti, Jukka; Loovis, Michael Edwin (European Journal of Adapted Physical Activity, 2016)
Physical fitness of individuals with intellectual disability (ID) is low compared to those without ID. Part of the missionof Special Olympics is to develop physical fitness. However, little is known about fitness levels of SpecialOlympics athletes. This study examined the fitness level of individuals who participated in Nordic Special OlympicsGames 2008 in Finland. The sample consisted of 59 Special Olympics athletes (44 men, 15 women, age 16-45)whose fitness scores were compared to INAS-athletes (International Association of Sport for para-athletes withID) and Finnish non-athletic individuals with ID. The fitness battery consisted of 8 items: BMI, sit-and-reachtest, stork stand, sit up, standing long jump, hand grip, shuttle run, and 1 mile/2 km walk test. BMI values werein the range of the nondisabled population. All other fitness values were below the means of the INAS-athletes, butabove the Finnish non-athletes. Based on this data which is supported by the existing literature, the level of fitnessof Special Olympics athletes needs further scrutiny. Given that the participants were Special Olympics athletes, whotrained regularly, the low fitness level is alarming. Therefore, a closer examination of the contents of physical fitnesstraining programs in Special Olympics is warranted.
Keywords: Special Olympics athlete; training; adults